PENGARUH KUALITAS LAYANAN, HARGA, DAN FASILITAS TERHADAP KEPUASAN PELANGGAN PADA USAHA CUCI KENDARAAN DIAMOND CARS WASH SUMBAWA - Irsadul Iba’ad; Abdul Salam (Jurnal Nusa Manajemen, 2026)
This study aims to analyze and test the influence of service quality, price, and facility variables on customer satisfaction at the Diamond Cars Wash vehicle washing business in Sumbawa. The background of this study is the increasing number of motorized vehicles in Sumbawa Regency which reached 201,710 units as of April 2025, thus creating a great opportunity for the vehicle washing service business. The methodology used in this study is a quantitative approach. The research sample consisted of 100 respondents who were Diamond Cars Wash customers, selected using a purposive sampling technique. Data collection was carried out by distributing questionnaires, and the collected data were analyzed using multiple linear regression analysis techniques with the help of SPSS. The results of the study indicate that partially, only the service quality variable has a positive and significant influence on customer satisfaction, with a t-value of 3.515 and a significance level of 0.001. 6Meanwhile, the price variable and the facility variable were found to have no significant influence on customer satisfaction. The results of the coefficient of determination test (Adjusted R Square) indicate that the three independent variables simultaneously explain only 9% of the customer satisfaction variable, while the remaining 91% is influenced by other factors not examined in this study.